Formulation and Development of Proniosomal Gel for Transdermal Delivery of Ketorolac Tromethamine - Farooqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study was to formulate and perform characterization, permeability enhancement studies, in-vitro, in-vivo evaluation of prepared formulation and stability studies of transdermal proniosomal (PN) gel for the anti-inflammatory and analgesic activity containing ketorolac tromethamine (KT). Materials and Methods: KT is heterocyclic acetic acid derivative with a molecular weight of approximately 255.27 g/mol, water-soluble and poorly absorbable, and act by inhibition of cyclooxygenase enzyme. PN gel formulations of KT were prepared from optimized PN suspension and effects of formulation variables such as solvents and surfactants on transdermal permeability profile were assessed. Carbopol 940 and dimethyl sulfoxide were added as gelling and penetration enhancing agents, respectively. Results and Discussion: PN gel formulations LCI-1-a showed better transdermal flux ex-vivo permeation (3.172 ± 0.041 μg/cm2/h) than LCI-2-b (2.651 ± 0.069 μg/cm2/h) and plain gel (1.941 ± 0.031 μg/cm2/h). PN gel LCI-1-a showed the highest drug release 94.048% in 17 h; marketed preparation showed drug release 90.987 in 17 h; plain gel showed drug release 41.154% in 10 h. The percentage inhibition of carrageenan-induced paw edema after 5 h of applying the LCI-1-a gel was found to be 63% while marketed preparation and plain gel showed 46.86% and 29%, respectively. Conclusion: The PN gel formulations showed good stability at refrigerated than room temperature after 3 months of storage. Among distinctive PN gel formulations, LCI-1-a (containing sodium cholate and isopropanol) showed promising results with respect to drug entrapment and percentage drug release. The formulations were subjected to pharmacokinetic and pharmacodynamic analysis by ex-vivo permeability studies; in-vivo anti-inflammatory, skin irritation studies, etc., and the results obtained were satisfactory.